Heat pump smoke waste heat recycling system of gas engine - ZHAI XIANGHE; XUE GUISHENG; LIU CHAO (2017)
The invention discloses a heat pump smoke waste heat recycling system of a gas engine. The heat pump smoke waste heat recycling system comprises a gas drive system, a water source heat pump system, a waste heat recycling system and a tail end energy supply system. The gas drive system is used for driving the water source heat pump system to work. The water source heat pump system is used for extracting heat on the water source side for supplying heat to users at the tail end. The waste heat recycling system is used for recycling heat of smoke discharged by the gas drive system. The tail end energy supply system is used for utilizing the heat recycled by the waste heat recycling system for supplying cold to the users at the tail end. Thus, by utilization of the scheme, the energy on the gas side and the water source side can be utilized for supplying heat and cold to the users at the tail end at the same time. 本发明公开了种燃气机热泵烟气余热回收系统，包括：燃气驱动系统、水源热泵系统、余热回收系统及末端供能系统；其中：所述燃气驱动系统，用于驱动所述水源热泵系统工作；所述水源热泵系统，用于提取水源侧的热量为末端